ANALYSIS OF THE INFLUENCE OF A COMPLEX OF MOBILE GAMES ON THE LEVEL OF MOTOR ACTIVITY OF MIDDLE SCHOOL STUDENTS IN GENERAL SECONDARY EDUCATION INSTITUTIONS (Physical Culture and Sport: Scientific Perspective, 2024)
The purpose of the article is to study the impact of a complex of mobile games on the level of motor activity of middle school students in general secondary education institutions. Methods. analysis of scientific and methodical literature, pedagogical experiment (declarative, formative), psychological and pedagogical observation; testing; methods of statistical data processing. The article analyzes the importance of health and recreational motor activity in the formation of the motor activity of middle school students and analyzes the pedagogical conditions that allow the pedagogical process to be carried out in the formation of the motor activity of middle school students using a complex of mobile games. The conducted research showed that in the modern educational space, the modernization of education is one of the priority tasks of the state. The transition from the generally accepted teaching of physical culture to the introduction of specialized physical culture at school is recognized as one of the key directions of updating the educational process. The effectiveness of the profile of physical culture in the school depends on the availability of the appropriate material and technical base, the development of sports traditions in the region, and the availability of qualified personnel. Implementation of specialized physical culture at school creates prerequisites for achieving high sports results and effective formation of motor activity of students. This initiative promotes a person-oriented approach to students and allows more flexible adaptation of the curriculum. Changes related to the introduction of specialized physical culture in schools help teachers to identify and develop the personal abilities of students, contributing to the formation of a competent personality based on them. The complex of mobile games, aimed at the development of physical qualities and improvement of motor activity, has a positive effect on the improvement of the motor activity indicators of middle school students and contributes to increasing their motivation and interest in physical education classes.
Keywords: motor activity; students of middle school age; complex of mobile games